Smoking habits: like father, like son, like mother, like daughter - Maria L. Loureiro; Anna Sanz-de-Galdeano; Daniela Vuri (Institute for the Study of Labor (IZA), 2006)
We analyze data from the 1994-2002 waves of the British Household Panel Survey to explore the influence of parental smoking habits on their children's smoking decisions. In order to account for the potential endogeneity of parental smoking habits we use instrumental variable methods. We find that mothers play a crucial role in determining their daughters' smoking decisions, while fathers' smoking habits are transmitted primarily to their sons
Keywords: 330; Rauchen; Familiensoziologie; Großbritannien